Evaluation of farm client participation in Michigan State University telfarm program - LaPorte, Jonathan P. (Kansas State University, 2022)
The TelFarm program is a Farm Management Information System (FMIS) operated by Michigan State University since 1963. It provides farm financial analysis, check-in and income tax estimation, depreciation scheduling, and routine recordkeeping support services to farm producers. Farm financial analysis is a primary service and provides publicly accessible industry comparison data for producer benchmarking. Enrollment in TelFarm has continued to decline since the 1980’s. Farm members that do participate in services rarely utilize the entirety of their subscriptions. The goal of this research project is to better understand clientele participation, service needs and expectations, and determine if any areas of improvement to TelFarm can be identified. The research method used was a survey conducted online and via phone interviews with active and non-active members of the TelFarm program. Results indicate that beginning farmers are less likely to enroll in TelFarm compared to established farmers. Fruit farms also indicated a strong aversion to membership compared to all other farm types. Recordkeeping services aimed at ensuring accuracy and creation of records for taxes is the primary expectation of members. Tax estimation and check-in meetings were ranked lowest of all services and viewed as a duplication of recordkeeping services. Beef, dairy, and field crop farms are more likely to participate in a farm financial analysis, but importance of industry comparisons for benchmarking was not a high expectation of any farm type. Member preference was to focus on profitability and obtaining an updated balance sheet.
Keywords: Agribusiness; Farm management information system; Farm finance; Financial analysis; Participation